Integrating Chemical Safety Education into Vocational and Professional Training for Disaster Risk Reduction in Industrial Settings - Digwijaya Anindyajati, Albertus; Syamsul Maarif; Ernalem Bangun (International Journal of Education, Vocational and Social Science, 2025)
The purpose of this paper is to explore the integration of chemical safety education into vocational and professional training systems in Indonesia, analyzed through a qualitative document review approach. The discussion connects theoretical and practical dimensions of education, technology, and environment to strengthen disaster risk reduction and resilience in industrial settings. Drawing inspiration from the educational perspectives of connectivism and constructivism, this paper emphasizes the need for learning strategies that reflect collaboration, experiential learning, and contextual understanding. By proposing the Integrated Vocational Safety Education Framework (IVSEF), the study provides a conceptual basis for aligning policy, pedagogy, and technology in building a culture of safety. The paper aims to inform future educational reforms that adapt to evolving ways of learning, communicating, and constructing knowledge in industrial education contexts.